Composition in the digital world : conversations with 21st century American composers - Raines, Robert, 1954- (Oxford University Press, 2015)
American composers are at the forefront of a renaissance in concert music, in the process expanding the very definition of the category. The impact of digital technology on the creative process and the unprecedented diversity of contemporary composers are arguably among the catalysts driving the rebirth. In this series of personal interviews with some of the most prominent composers of art music currently working on the American music scene, composer and educator Robert Raines leads the intimate conversations through subjects ranging from the source of inspiration to work habits, the realities.